2004
DOI: 10.1063/1.1738414
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional numerical investigations of small-amplitude disturbances in a boundary layer at Ma=4.8: Compression corner versus impinging shock wave

Abstract: Two-dimensional direct numerical simulations and linear stability theory investigations have been carried out for a compression ramp at Maϭ4.8 and compared to earlier results of a laminar boundary layer with impinging shock wave. The inflow parameters in both flows were identical; the ramp angle of the compression corner was chosen to cause a separation bubble, which has exactly the same length compared to the case with impinging shock. It turned out, that the two cases are almost identical for the base flow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…A 2D case is run for a 6 • compression ramp at M = 4.8 and Re = 6, 843. Good agreement is obtained with Ludeke and Sandham [3] and Pagella et al [5]. Simulations are then run in 2D at 12 • at M = 4.8 and Re=3,422 and 6,843.…”
Section: Resultssupporting
confidence: 75%
“…A 2D case is run for a 6 • compression ramp at M = 4.8 and Re = 6, 843. Good agreement is obtained with Ludeke and Sandham [3] and Pagella et al [5]. Simulations are then run in 2D at 12 • at M = 4.8 and Re=3,422 and 6,843.…”
Section: Resultssupporting
confidence: 75%
“…Pagella et al 27 investigated the differences between a compression corner and a laminar boundary layer with impinging shock wave and found (a) the two configurations to be identical apart from near the corner and the impinging shock and (b) good agreement between the LST and DNS approaches, albeit for weaker interaction than those considered here. For the present study, the amplitude of the disturbances at different x-locations are normalised with the amplitude at the separation point allowing a direct comparison between DNS and LST.…”
Section: Resultsmentioning
confidence: 66%
“…In this work, the response of the initially laminar boundary layer to artificially introduced smallamplitude disturbances was investigated and the results compared well with those of linear stability theory. This work was later extended to the case of a 2D compression ramp flow, also at Mach 4.8 ͑Pagella et al 15 ͒, showing that, when the impinging shock and the shock created by the compression ramp have the same strength, the characteristics of SBLI were identical ͑validating the so-called free interaction concept originated by Chapman et al 16 ͒. This latter work also demonstrated that the response to small-amplitude disturbances was practically identical.…”
Section: Introductionmentioning
confidence: 88%